Quantum-dot sensitized hierarchical NiO p–n heterojunction for effective photocatalytic performance. Issue 50 (11th November 2022) - Khan, Junaid; Ali, Gohar; Samreen, Ayesha; Ahmad, Shahbaz; Ahmad, Sarfraz; Egilmez, Mehmet; Amin, Sadiq; Khan, Nadia
Abstract : A facile and low-cost pseudo successive ionic layer adsorption and reaction technique was used to deposit cadmium sulfide quantum dots (CdS QDs) on hierarchical nanoflower NiO to form effective and intimate NiO/CdS, p–n heterojunctions. Abstract : A facile and low-cost pseudo successive ionic layer adsorption and reaction technique was used to deposit cadmium sulfide quantum dots (CdS QDs) on hierarchical nanoflower NiO to form an effective and intimate NiO/CdS p–n heterojunction system. The synthesized hierarchical p–n heterojunctions demonstrated effective photocatalytic activity due to the enhanced separation and transport of photogenerated charge carriers compared to standalone NiO. The dye degradation efficiency of optimized CdS QDs that form p–n heterojunctions was examined by rhodamine B and methylene blue dyes under UV-vis irradiation. The improved photocatalytic performance can be accredited to a large morphological surface, and the successful deposition of CdS QDs to form an active p–n junction for efficient charge separation and migration. The morphological, structural, optical, charge transfer and photocatalytic characteristics of synthesized hierarchical p–n junction photocatalyst were studied by scanning electron microscopy, UV-visible absorbance, X-ray diffraction, photoluminescence spectroscopy, electrochemical spectroscopy, and Fourier transform infrared spectra. Additionally, scavenging experiments were performed to find out the energetic species taking part in dye-degradation, and a rational reaction mechanism has been proposed.